Quality Control and Stability Testing of Arq Formulations of Unani Pharmacopeia of India Using HPTLC and GC-MS. (19th June 2020) - Zahiruddin, Sultan; Parveen, Abida; Khan, Washim; Ibrahim, Mohammad; Akhtar, Jamal; Khan, Asim Ali; Ansari, S H; Ahmad, Sayeed
Abstract: Background: There is an increasing global demand for traditional medicines because of their efficacy, ease of availability, and few or no side effects. The Unani medicines have long been used in India and abroad for various disorders and diseases. Arqiyat (Arq; distillate) is one of the most widely used Unani formulation prepared by simple distillation from single or combination drugs. Objective: In the present investigation, an attempt has been made to generate data for quality control and stability testing of Arq formulations of the Unani Pharmacopeia of India that includes only three Arq formulations. Method: Arq-e-Nana (AeN), Arq-e-Gazar (AeG), and Arq-e-Brinjasif (AeB) were prepared through hydrodistillation. Quality control and stability analysis were performed by using HPTLC and GC-MS. Results: Dichloromethane extract of AeB showed maximum of 10 bands at different retardation factor values; however, there are 7 bands in AeN as well as in AeG. GC-MS analysis showed presence of 10 metabolites in AeG, 8 in AeN, and 9 in AeB. Stability studies showed that the shelf life of Arq formulations would be enhanced at refrigeration (5 ± 2°C) conditions. Conclusions: The present study highlights quality control and stability analysis of Arq formulations of Unani Pharmacopeia of India using HPTLC and GC-MS.